Efficacy of new and existing chemical biopreparations in controlling apple red spider mite (Panonychus ulmi Koch) - Raxmanov Ahliddin; Sulaymonova Gulasal (E3S Web of Conferences, 2023)
This article provides information on the damage caused by the apple red spider mite (Panonychus ulmi Koch) in apple orchards and methods of combating it. Apple red spider mite (Panonychus ulmi Koch) is the most dangerous pest of orchards and other crops in other European countries. This pest can kill more than half of the crops in some fields. It is said that spider mite kills 6-10% of the total crop in normal years, and even 14% in some years. The apple red spider mite (Panonychus ulmi Koch) is more dangerous and harmful than other spider mites. In the world, more than 150 species of spider mites are recorded as the main pests of crops. Microbiological biopreparations Bioslip BV (Beauveria bassiana) was found to be a microbiological biopreparation with a strong effect on arachnids that cause damage in seed orchards at the rate of 3.0 l/ha. The effect of microbiological biopreparations can be achieved on the third-seventh and fourteenth-twenty-first day. The Bioslip BV (Beauveria bassiana) 3.0 l/ha biopreparation and Bioslip BT (Bacillus thuringiensis) (toxin crystals in 1 g) (1.0 l/ha) biopreparations taken for the experiment were analyzed from the 3rd day of use. According to the results of the conducted research, in the variant where Bioslip BV (Beauveria bassiana) 3.0 l/ha biopreparation was used, the biological efficiency was 44.2% on the 3rd day after using the biopreparation, 72.3% on the 7th day, and 72.3% on the 14th day. 73.9% on the 21st day, and 60.2% on the 21st. Bioslip BT microbiological biopreparation (Bacillus thuringiensis) (toxin crystals in 1 g) (1.0 l/ha) 86.7% on the 3rd day, 85.8% on the 7th day, 88.9% on the 14th day, and on the 21st it was 87.5%.